Eça de Queirós no audiovisual - Sobral, Filomena Antunes (2011)
Knowing that the literary adaptation is a phenomenon that crosses history, and also knowing that most of the literary transpositions have its roots in canonical 19th century novels, we begin this essay by drawing a map of the adaptations of the work of the Portuguese writer Eça de Queirós for film and television language. At the same time, we emphasize the dramatic potential of the writer’s literary inheritance. Lastly, we point out that the narrow collaboration between literature and audiovisual, besides revitalizing the classic narratives, also allows cultural democratization of the Portuguese literary tradition for the present generations.